Enhanced cross‐shelf exchange by tides in the western Ross Sea. Issue 21 (14th November 2013) - Wang, Q.; Danilov, S.; Hellmer, H.; Sidorenko, D.; Schröter, J.; Jung, T.
<x xml:space="preserve">Abstract</x> [1] The western Ross Sea is one of the key sites for cross‐shelf water exchange around Antarctica. The mechanism through which tides affect the cross‐shelf exchange in the northwestern Ross Sea is investigated using numerical simulations. Tides are found to increase the high‐salinity shelf water (HSSW) outflow through the impact on the warm water intrusion of open ocean origin. The residual tidal currents are onshore along the Modified Circumpolar Deep Water pathway and therefore enhance its intrusion. Lighter ambient water adjacent to the HSSW increases the cross‐flow density gradient, thus strengthening the HSSW export. At the same time, the onshore residual current and increased dilution of the HSSW have the potential to reduce the export rate. Owing to the existence of opposite tidal effects, the strongest HSSW export happens at the intermediate tidal forcing strength. The amplification of tides on cross‐shelf exchange indicates that the relevant dynamical processes should be simulated or parameterized in climate models in order to adequately predict the ocean.